Alpha-Synuclein Loss in Spinal Muscular Atrophy - Acsadi, Gyula (2010)
Spinal muscular atrophy, the most prevalent hereditary motor neuron disease, is caused by mutations in the survival motor neuron (SMN) 1 gene. A significant reduction in the encoded SMN protein leads to the degeneration of motor neurons. However, the molecular events leading to this process are not well understood. The present study uses a previously developed neuronal cell culture model of spinal muscular atrophy for a multiplex transcriptome analysis. Furthermore, gene expression analysis was performed on in vitro cell cultures, as well as tissue samples of spinal muscular atrophy patients and transgenic mice. RNA and subsequent Western blot protein analyses suggest that low SMN levels are associated with significantly lower alpha-synuclein expression. Examination of two genes related to vesicular transport showed a similar though less dramatic decrease in expression. The 140-amino acid protein alpha-synuclein, dominant mutations of which have previously been associated with an autosomal dominant form of Parkinson's disease, is strongly expressed in select neurons of the brain. Although not well understood, the physiologic functions of alpha-synuclein have been linked to synaptic vesicular neurotransmitter release and neuroprotection, suggesting a possible contribution to Smn-deficient motor neuron pathology. Furthermore, alpha-synuclein may be a genetic modifier or biomarker of spinal muscular atrophy.